Learning Module on Human Trafficking to Improve Learners” Understanding of Human Trafficking - Vincentius Ferrer Dede; Christina Ismaniati (Universitas Pendidikan Ganesha, 2024)
Students lack understanding of human trafficking material well and corectly. This is due to the absence of learning resources in learning the material of human trafficking independently. This research aims to develop a printed learning module that is feasible, practical and effective to improve understanding of human trafficking. The research model used is Atwi Suparman's Instructional Development Model. The sample in the study are 80 students of class XI. Data collection through tests, interviews and questionnaires. Data analysis used quantitative descriptive analysis techniques. The research produced a learning module that is feasible, practical and effective. In the aspect of media feasibility obtained a score of 3.2 with the predicate very feasible. The material feasibility aspect obtained a score of 3.5 with the predicate very feasible. The practicality of the module obtained a score of 3.7 with the predicate very practical. Learning modules effectively improve understanding. Based on the N-gain test, students' understanding has increased as obtained from the average N-gain score of 0.6 with a fairly effective category. Thus, this learning module is effective enough to improve understanding of human trafficking. The implication of this research is the availability of independent learning resources in the form of printed modules for students to improve understanding of human trafficking.